High-efficiency solution-processable platinum complex luminescent material constructed by AIE-HLCT ligand and application of high-efficiency solution-processable platinum complex luminescent material

CN119409737APending Publication Date: 2025-02-11LIANYUNGANG TECHN COLLEGE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411622286.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

[0003]尽管AIE-Pt配合物由于其多样的配位模式和分子结构而具有多种光电性能,具有广阔的应用前景,然而,现有的关于AIE-Pt配合物的研究存在一定的局限性,首先,这些研究只涵盖了一小部分AIE-Pt配合物,缺乏全面系统的研究;其次,近年来新型AIE-Pt配合物的开发进展以及AIE新机制及其应用的探索需要进一步深化;最后,在以往的相关研究中,缺乏对分子结构、性质和应用之间关系的全面分析;另外,通过溶液加工制造的OLED由于其在大面积和灵活柔性的器件应用方面的潜力,其需求量巨大;溶液加工比真空蒸镀加工更有优势,因为前者易于加工,并且使用低成本的仪器,如旋转镀膜,叶片铸造和喷墨印刷,同时避免了高温和高压等苛刻的制造条件;

Benefits of technology

[0017] (1) Through the flexible AIE-HLCT ligand synergistic metal Pt, the helical spatial structure AIE-Pt complex PyBT-Pt-THD is invented, and it has AIE characteristics, which can eliminate the aggregation-induced quenching effect (ACQ) and further improve luminescence Efficiency, while effectively increasing solubility, making it reach solution processing, and laying the foundation for future commercialization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119409737A_ABST
    Figure CN119409737A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of platinum complex phosphorescent materials, and particularly discloses an efficient solution-processable platinum complex luminescent material constructed by an AI E-HLCT ligand and application of the efficient solution-processable platinum complex luminescent material constructed by the AI E-HLCT ligand, the efficient solution-processable platinum complex luminescent material constructed by the AI E-HLCT ligand is prepared by taking an aggregation-induced hybrid local charge transfer (AI E-HLCT) material N, N '-(pyrimidine-4, 6-diyl-bis (4, 1-phenylene)) bis (N-([1, 1'-biphenyl]-4-yl)-[1, 1 '-biphenyl]-4-amine) as a CN bidentate ligand; 2, 2, 6, 6-tetramethyl-3, 5-heptanedione with a solubilizing function is adopted as the auxiliary ligand; the AI E-Pt complex PyBT-Pt-THD with the spiral space structure is invented through cooperation of a flexible AI E-HLCT ligand and metal Pt, and the AI E-Pt complex PyBT-Pt-THD has the AI E characteristic, can eliminate the aggregation-induced quenching effect (ACQ) and further improve the luminous efficiency, and meanwhile, the solubility is effectively improved, so that the AI E-Pt complex PyBT-Pt-THD can be processed in a solution.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of platinum complex phosphorescent materials, and in particular relates to AIE-HLCT ligands to construct highly efficient solution-processable platinum complex luminescent materials and applications thereof. Background Art

[0002] Transition metal materials with aggregation-induced emission (AIE) properties have brought new opportunities for the development of biological probes, optoelectronic materials, stimuli-responsive materials, sensors and detectors. Among them, AIE-platinum (Pt) complexes have different photoelectric properties due to the differences in ligand number, ligand structure, oxidation state, coordination mode, geometry, stacking state and aggregation environment. These changes show significant research and application value for AIE platinum complexes.

[0003] Although AIE-Pt complexes have a variety of optoelectronic properties due to their diverse coordination modes and molecular structures and have broad application prospects, the existing research on AIE-Pt complexes has certain limitations. First, these studies only cover a small number of AIE-Pt complexes and lack comprehensive and systematic research; second, the development progress of new AIE-Pt complexes in recent years and the exploration of new AIE mechanisms and their applications need to be further deepened; finally, in previous related studies, there is a lack of comprehensive analysis of the relationship between molecular structure, properties and applications; in addition, OLEDs manufactured by solution processing are in huge demand due to their potential for large-area and flexible device applications; solution processing has advantages over vacuum evaporation processing because the former is easy to process and uses low-cost instruments such as spin coating, blade casting and inkjet printing, while avoiding harsh manufacturing conditions such as high temperature and high pressure;

[0004] Despite significant progress in the development of solution-processed OLEDs, their efficiency and lifetime still lag behind those of vacuum-processed devices. Summary of the invention

[0005] The purpose of the present invention is to provide an AIE-HLCT ligand to construct an efficient solution-processable platinum complex luminescent material and its application. A new AIE-Pt complex is developed through the AIE-HLCT ligand, aiming to fundamentally enrich and develop solution-processable AIE-Pt complex luminescent materials, maximize the luminescent efficiency of AIE-Pt complex luminescent materials in OLEDs, and solve the key problems such as the scarcity of solution-processable AIE-Pt luminescent materials, low luminescent efficiency, and severe luminescent efficiency roll-off.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] AIE-HLCT ligands are used to construct highly efficient solution-processable platinum complex luminescent materials, including:

[0008] Aggregation-induced hybrid localized charge transfer (AIE-HLCT) material N,N'-(pyrimidine-4,6-diylbis(4,1-phenylene))bis(N-([1,1'-biphenyl]-4-yl)-[1,1'-biphenyl]-4-amine) as C^N bidentate ligand;

[0009] The auxiliary ligand is 2,2,6,6-tetramethyl-3,5-heptanedione which has a solubilizing function;

[0010] The structural framework exhibits an asymmetric vibration mode;

[0011] The chemical structure of the luminescent material is shown below:

[0012]

[0013] Preferably, the spatial stacking form of the luminescent material is a spiral configuration.

[0014] The AIE-HLCT ligand is used to construct an efficient solution-processable platinum complex luminescent material, and is used as a luminescent material dopant in preparing a luminescent layer of a solution-processed luminescent device.

[0015] Preferably, the solution-processed light-emitting device has a light emission wavelength of 562 nm in a 2wt% doped 26DCzPPy film, a maximum external quantum efficiency of 35.3%, and a maximum external quantum efficiency of 29.1% at a brightness of 5000.

[0016] Compared with the prior art, the present invention has the following beneficial effects:

[0017] (1) Through the flexible AIE-HLCT ligand and the coordination of metal Pt, the helical spatial structure AIE-Pt complex PyBT-Pt-THD was invented. It has AIE properties, which can eliminate the aggregation-induced quenching effect (ACQ) and further improve the luminescence efficiency. At the same time, it effectively increases the solubility, making it solution-processable and laying the foundation for future commercialization.

[0018] (2) Selecting HLCT ligands, which can effectively utilize singlet / triplet excitons through high-position anti-gap crossing, realize an effective spin coupling-assisted intergap crossing process, thereby promoting phosphorescence emission and effectively mitigating the impact of non-radiative transitions.

[0019] (3) The spatial stacking form of the constructed Pt complex is a rare helical mode, and this helical-spatial structural engineering can effectively improve the carrier transport efficiency.

[0020] (4) Constructing heterogeneous Pt complexes with 2,2,6,6-tetramethyl-3,5-heptanedione as an auxiliary solubilizing ligand. This small skeleton unit can effectively enhance the charge transfer between triplet metal ligands ( 3 MLCT), while increasing the material solubility, effectively ensure the luminous efficiency.

[0021] (5) The molecular structure is simple, easy to synthesize, and the preparation cost is low. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 Schematic diagram of the hydrogen spectrum of the ligand PyBT in Example 1 of the present invention;

[0023] Figure 2 Schematic diagram of the hydrogen spectrum of the complex PyBT-Pt-THD of Example 1 of the present invention;

[0024] Figure 3 This is a schematic diagram of the analysis of the quantum chemical calculation results of the ligand PyBT in Example 1 of the present invention;

[0025] Figure 4 Schematic diagram of HOMO and LUMO energy level analysis of the ligand and complex of the present invention;

[0026] Figure 5 It is a schematic diagram of the solid luminescence behavior of the ligand PyBT and the complex PyBT-Pt-THD in Example 1 of the present invention under irradiation with light of 365 nm wavelength;

[0027] Figure 6 Schematic diagram of the single crystal structure and spatial stacking mode of PyBT-Pt-THD in Example 1 of the present invention;

[0028] Figure 7 This is a schematic diagram of processing an OLED device with a PyBT-Pt-THD solution in Example 1 of the present invention;

[0029] Figure 8 Schematic diagram of the synthesis route of PyBT-Pt-THD in Example 1 of the present invention. DETAILED DESCRIPTION

[0030] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] Example 1: Synthesis of the helical spatial structure platinum complex luminescent material PyBT-Pt-THD, such as Figure 8 As shown;

[0032] Synthesis of ligand PyBT

[0033] 4,6-dibromopyrimidine (500 mg 2.10 mmol, 1.0 eq.), (4-(di([1,1'-biphenyl]-4-yl)amino)phenyl)boronic acid (1.85 g, 4.20 mmol, 2.2 eq.), K 2 CO 3 (2.32g,16.8mmol,8eq.), Pd(PPh 3 ) 4 (218 mg, 0.189 mmol, 0.06 eq.) was added to toluene / ethylene alcohol / water (50 / 5 / 5 mL). The mixture was stirred at 95°C for 24 h, cooled to room temperature, extracted with dichloromethane, and purified by column chromatography using a mixture of petroleum ether / dichloromethane (1:2) as the eluent to obtain a waxy solid (855 mg) with a yield of 46%.

[0034] 1 H NMR (400MHz, Chloroform-d): δ / ppm=9.21(s,1H),8.06(d,J=6.9Hz,4H),7.64–7.57(m, 11H),7.55(s,5H),7.45(dd,J=8.4,6.9Hz,8H),7.28(d,J=6.5Hz,8H).MODI-TOF-MS:m / z calculated for C 64 H 46 N 4 [M] + :871.1000; found:871.3722.Elementalanalysis(%)for C 64 H 46 N 4 :C 88.25,H 5.32,N 6.43; found:C 88.17,H 5.39,N 6.41. (NMR spectrum see Figure 1 ).

[0035] Synthesis of the complex PyBT-Pt-THD

[0036] In N 2Under atmosphere, PyBT (200 mg, 0.30 mmol, 1.0 eq.) and potassium tetrachloroplatinate (200 mg, 0.48 mmol, 1.6 eq.) were dissolved in acetic acid (70 mL), refluxed for 3 d, cooled to room temperature, filtered off the black solid, washed with MeOH (20 mL*3), and air-dried. The crude product was added to a DCM / MeOH solution (40 / 10 mL) of 2,2,6,6-tetramethyl-3,5-heptanedione (THD 62 mg, 0.33 mmol, 1.1 eq.), and then tBuOK aqueous solution (2 M, 5 mL) was added. Refluxed for 24 h, the reaction solution was removed under reduced pressure, and the crude product was dissolved in DCM. The organic layer was washed with brine and filtered through anhydrous MgSO 4 Dry, filter, and evaporate to dryness. Then use n-heptane and CHCl 3 The residue was purified by column chromatography as an eluent to obtain an orange solid (88 mg) in a yield of 26%.

[0037] 1 H NMR (400MHz, Chloroform-d): δ / ppm=9.41(s,1H),8.11–7.96(m,1H),7.66(s,1H),7.63–7.52(m,15H),7.45(td,J= 7.7,2.7Hz,9H),7.39–7.21(m,16H),7.00–6.86(m,1H),5.73(s,1H),1.25(s,10H),0.90(s,8H).MODI-TOF-MS:m / z calculated forC 75 H 64 N 4 O 2 Pt[M]+:1247.4677; found:1247.4470.Elemental analysis(%)forC 75 H 64 N 4 O 2 Pt: C 72.16, H 5.17, N 4.49, O 2.56, Pt 15.63; found: C 72.17, H 5.73, N 4.43, O 2.61, Pt 15.67. (NMR spectrum see Figure 2 ).

[0038] Embodiment 2:

[0039] Theoretical calculations of the ligand PyBT and the complex PyBT-Pt-THD: All calculations were performed using the Gaussian 16 software package by DFT theoretical calculations. The Pt(II) complex was simulated by DFT to perform geometry optimization on the hybrid functional energy levels of PBE1PBE-D3 / LANL2DZ (Pt atoms) and PBE1PBE-D3 / 6-311g+(d,p) (H, C, N and O atoms) in the ground state S 0 structure;

[0040] For singlet and triplet transitions, the electron density distribution of each atom in the highest occupied orbital and the lowest unoccupied orbital of the frontier was obtained by Mulliken cluster analysis, and the MLCT characteristics of each assignment in the absorption and emission process were calculated, which effectively analyzed the ligand and the complex.

[0041] The results show that the singlet excited state S 1 With the triplet excited state T 1 The energy level difference ΔE(S1T1) is 0.41eV; and S 1 State and T 1 The self-selected coupling matrix value (SOC) between states Only 0.0768cm -1 Such a large energy level difference and a negligible SOC value make it difficult for the ligand to pass through T like thermally activated delayed fluorescence (TADF) materials. 1 state, effectively realizing the reverse inter-slot crossing process (RISC) to reach S 1 Although its ΔE(S 1 T 1 ) value is large, but ΔE(S 1 T 4 ) is only 0.09 eV, and to our surprise, the triplet excited state T 3 With T 4 The energy level difference between them is negligible (only 0.0001), which makes T 3 and T 4 The double triplet excited state forms a degenerate triplet excited state, and its and Up to 0.3745 and 0.4466cm -1 , which enables the ligand PyBT to achieve effective h RISC process( Figure 3 a);

[0042] Therefore, the luminescence mechanism of the ligand PyBT can be reasonably inferred, such as Figure 3 As shown in b, the triplet excited state behaves in a degenerate manner, forming T 3 / 4 , so that the triplet excitons can be transported through h under the strong SOC RISCThe process transitions to the singlet state S 1 state, thereby emitting radiation. This luminescence behavior is a typical HLCT characteristic material;

[0043] NTO analysis found that ( Figure 3 c), S of ligand PyBT 1 The charge distribution of the state is based on the CT state and the LE state at the acceptor end (CT+LE A ) mainly participate in h RISC T of process 3 State and T 4 The state is distributed on both sides of the donor benzidine in the form of donor end LE state (LED), which is also the T 3 State and T 4 state, can be degenerated to form a degenerate triplet excited state T 3 / 4 The key to

[0044] Next, the HOMO and LUMO energy levels of the ligand and complex were analyzed, such as Figure 4 As shown in a, compared with the ligand ground state (S 0 )CT+LE A The charge distribution of the complex PyBT-Pt-THD is disturbed by the metal Pt, making S 0 The states are mainly metal-ligand charge transfer (MLCT) and intra-ligand charge transfer (ILCT), and the main contribution of metal Pt is concentrated on the HOMO energy level, which is 4.36%, while the LUMO contributes only 0.49%. Such a small metal contribution is completely opposite to the traditional Pt complex. This also indirectly shows that the HLCT ligand will not cause a significant change in its original luminescence mechanism due to the introduction of metal. However, the introduction of metal slightly raises the HOMO and lowers the LUMO. Its band gap is reduced to 2.89eV compared with 3.36eV ​​of the ligand PyBT, indicating that the luminescence wavelength of PyBT-Pt-THD has a significant red shift compared with PyBT.

[0045] After the metal is introduced, due to the d 8 The electronic configuration makes the coordination part obviously planarized ( Figure 4 b), the RMSD between the ground state and the excited state of the complex PyBT-Pt-THD is significantly reduced compared with the ligand PyBT. Reduce to This result is mainly due to the weakening of the overall vibration relaxation of the molecular structure skeleton after the coordination of Pt atoms. Such a small RMSD also indicates that the structural relaxation process between the ground state and the excited state is significantly accelerated.

[0046] In order to further analyze the effect of coordination of metal Pt atoms on weakening the structural distortion between the ground state and the excited state and weakening the coupling effect, the reorganization energy (λ) and Huang-Rhys factor (H-RF) were calculated and analyzed, such as Figure 4 As shown in c and d, the reorganization energy of the PyBT-Pt-THD complex under vibration mode is S 0 State to T 1 State transition reorganization energy (1153cm -1 ) and T 1 State to S 0 State transition reorganization energy (1166cm -1 ), so the total reorganization energy is 2319 cm -1 ;

[0047] We further refined T 1 State to S 0 The Huang-Rhys factor of the state is 1 and S 0 During the structural vibration conversion process, the -1 The vibration contribution above the frequency is close to 0, and the vibration coupling effect on the transition behavior is small. Therefore, the vibration relaxation behavior caused by the main structural distortion is mainly concentrated in 0-100cm -1 In the low frequency vibration range;

[0048] Among them, the maximum Huang-Rhys factor of PyBT-Pt-THD is 8.55, which mainly comes from the 2.0 cm -1 Vibration frequency and vibration model analysis show that this result is mainly caused by benzidine at the donor end, whose structural deformation is mainly torsion and bending vibration, and other parts of the molecular structure are only slight skeleton stretching vibration. For this reason, PyBT-Pt-THD has a smaller vibration reorganization energy. Therefore, the introduction of Pt atoms will not only not cause obvious deformation effect on the ligand PyBT, but also effectively inhibit the vibration at the C^N coordination site and weaken the transition vibration coupling, thereby effectively reducing the reorganization energy and weakening the Franck-Condon factor, thereby reducing the non-radiative decay rate;

[0049] In order to deeply reveal the excited state characteristics and electronic properties of PyBT-Pt-THD, time-dependent DFT (TDDFT) calculations and natural transition orbitals (NTOs) analysis were performed. Figure 4 e, g), PyBT-Pt-THD singlet excited state S 1 With the triplet excited state T 1 The energy level difference ΔE(S 1 T 1) is 0.33 eV. The excited state energy levels indicate that the singlet excited state and triplet excited state involved in the interslot crossing process (ISC) include not only S 1 (2.4940eV) and T 1 (2.1571 eV), also involves the triplet excited state T 2 (2.2910eV) energy level. The singlet / triplet spin-orbit coupling (SOC) clarifies the strength of the ISC process. 1 →T 2 Transition SOC (129.817cm -1 ) Compared with S 1 →T 1 Transition SOC (7.224cm -1 ) is significantly enhanced, indicating that the ISC process has a S 1 →T 1 Direct SOC and S 1 →T 2 The characteristics of indirect SVC (spin vibration coupling) combined with

[0050] T 1 and T 2 The highest occupied natural transition orbital (HONTO) and the lowest unoccupied natural transition orbital (LUNTO) are mainly 3 MLCT / 3 The ILCT state charge is delocalized over the entire molecule, and T 1 State and T 2 The distribution behavior of the states inherits the degenerate triplet excited state T of the ligand PyBT. 3 / 4 The complementary characteristics also fully demonstrate that the electronic properties of the ligand fully affect the complex. In summary, the luminescence mechanism of the ligand PyBT-Pt-THD can be reasonably inferred, such as Figure 4 f, its S 1 The state is directly affected by SOC on T 1 state, and acts on T through indirect SVC 2 state;

[0051] Moreover, due to the smaller ΔE(T 1 T 2 ), so that T 2 To T 1 The internal conversion (IC) process is very fast. It is worth noting that this multi-threaded ISC process is brought about by the HLCT characteristic ligand. Pt complexes have not had such a phenomenon in the past. This is the first case reported so far.

[0052] Example 3: Solid-state luminescence properties of ligand PyBT and complex PyBT-Pt-THD

[0053] The solid luminescence behavior under 365nm wavelength shows that the ligand PyBT solid exhibits sky blue light, while the complex PyBT-Pt-THD solid exhibits orange-red light.

[0054] Example 4: Single crystal test of the complex PyBT-Pt-THD

[0055] X-ray single crystal diffraction studies revealed its single crystal structure and stacking packing motif, such as Figure 6 As shown;

[0056] In the crystalline state, PyBT-Pt-THD adopts an unexpected coplanar conformation, and the DA dihedral angle is close to zero after the coordination of metal platinum. This result is basically consistent with the quasi-planar conformation of the optimized PyBT-Pt-THD monomer in the gas phase.

[0057] This indicates that the stabilizing effect of the C^N…Pt bond stabilizes this coplanar conformation through strong interactions between molecules. The molecules in the crystal are arranged tightly and orderly, and a universal dimer configuration can be extracted from the single crystal structure. The stacking distance between monomers 1 and 2 is very close, and their spatial face-to-face arrangement shows a tilt, with a face-to-face tilt angle of 26°.

[0058] In addition, multiple CH…N intermolecular hydrogen bonds in the ligands interact at the periphery, further stabilizing the dimer structure. Then, the dimers are stacked along the longitudinal axis of the molecule with almost the same interplanar spacing. In addition, there are also multiple CH…N interactions between these layered structures, forming a dense long-range staggered helical structure in the crystal state, and the helical depth is This regular deep spiral structure is more conducive to carrier transport.

[0059] Example 5: Fabrication of light-emitting devices based on PyBT-Pt-THD materials and testing of light-emitting performance

[0060] The structure of the organic electroluminescent device is:

[0061] ITO / PEDOT:PSS(30nm) / PVK(30nm) / 26DCzPPy:PyBT-Pt-THD(dopedornon-doped,40nm) / TmPyPB(50nm) / LiF(1nm) / Al(100nm);

[0062] The hole injection layer is polyethylene dioxythiophene / poly(p-styrene sulfonic acid) (PEDOT:PSS) (Bayer Batron P4083); the hole transport layer is polyvinyl carbazole (PVK); the electron transport layer is 1,3,5-tri(3-pyridyl-3-phenyl)benzene (TmPyPB); the light-emitting layer is a blended coating of the guest material (PyBT-Pt-THD) and the host material 2,6-bis[3-(9H-carbazole-9-yl)phenyl]pyridine (26DCzPPy); the electron injection layer is lithium fluoride (LiF); and the cathode layer is aluminum (Al);

[0063] The device fabrication procedure is as follows: the ITO glass was cleaned with isopropanol, acetone, and deionized water in sequence, dried in a drying oven, and treated with UV-ozone for 15 min at 100°C. After that, 30 nm of PEDOT:PSS, 30 nm of PVK, and 40 nm of the luminescent layer were spin-coated. Then, 50 nm of TmPyPB, 1 nm of LiF, and 100 nm of Al were evaporated in sequence. The luminescent area of ​​the device was 0.04 cm 2 ;

[0064] The thickness of the hole injection layer, hole transport layer and light-emitting layer was measured by a probe-type surface profiler (Dektak-XT from Bruker). The thickness and deposition rate of TmPyPB, LiF and Al were measured by a thin film coating controller (SQC-310C from Inficon). The deposition rates of TmPyPB, LiF and Al were and All operations were performed in a nitrogen glove box;

[0065] The electroluminescence spectrum (EL) was measured using a PR-735 spectroradiometer from PhotoResearch; the current-voltage (IV) curve and the luminescence intensity-voltage (LV) curve were measured using a Keithley2400 source measurement unit from Tektronix, and the external quantum efficiency was calculated based on the electroluminescence spectrum, current density, and brightness, assuming Lambert emission;

[0066] The electroluminescence spectrum and EQE-L curve of the light-emitting device made of PyBT-Pt-THD material are shown in Figure 2. Figure 7 As shown in Table 1;

[0067] Table 1

[0068]

[0069] a)The EQE value at the maximum,1000cd·m -2 , 50000cd·m -2 ,1000cd·m-2 , respectively;

[0070] The solution-processed device based on PyBT-Pt-THD has an emission wavelength of 562nm in a 2wt% doped 26DCzPPy film, a maximum external quantum efficiency (EQE) of 35.3%, and an EQE of nearly 30% (29.1%) at 5000 luminance, which is unprecedented and compared with other related materials. Figure 7 fg and Tables 2 and 3;

[0071] Table 2

[0072] ELperformanceofhighlyefficiencysolution-processedyellowphosphorescenceOLEDs.

[0073]

[0074]

[0075] a Not report.

[0076] Table 3

[0077] Summary of the device performance of yellow vacuum-processed OLEDs

[0078]

[0079]

[0080]

[0081] The present invention uses a polyaromatic hydrocarbon ligand with HLCT characteristics and C^N coordination and flexible auxiliary units to synergistically enhance the AIE characteristics, wherein the C^N coordination unit is 4,6-diphenylpyrimidine and the flexible auxiliary unit is an aromatic amine electron-donating functional group, to construct an AIE-HLCT ligand PyBT, and the auxiliary ligand uses 2,2,6,6-tetramethyl-3,5-heptanedione with a solubilizing function. Through the effective introduction of metal Pt, an efficient solution-processable platinum complex luminescent material PyBT-Pt-THD with AIE characteristics is developed. The material can effectively promote phosphorescence emission through the HLCT ligand to achieve effective spin-vibration coupling assisted intergap crossing (SVC) process, thereby effectively suppressing non-radiative transitions;

[0082] The key to constructing an AIE-Pt complex luminescent material that is highly luminescent, stable, and solution-processable is to increase the molecular solubility while improving the radiation transition rate and suppressing the exponential increase in the non-radiation transition rate, thereby alleviating the contradiction between the introduction of solubilization sites and the reduction in efficiency. The spiral-space structure of the present invention can effectively adjust the contradiction and greatly improve the carrier transfer efficiency through the spiral skeleton, thereby improving the performance of OLED devices;

[0083] This is the first Pt complex phosphorescent material device that simultaneously possesses AIE properties, multithreaded intergap crossing, and spiral spatial arrangement.

[0084] exist Figure 3 In the figure, a is the energy level diagram of the spin-orbit coupling (SOC) matrix element; b is the mechanism description; c is the S 1 and T 1 -T 4 The natural transition orbital (NTO) distribution of the states;

[0085] exist Figure 4 In the figure, a is the energy level of PyBT and PyBT-Pt-THD, frontier molecular orbital diagram (equivalent value: 0.02); b is a schematic diagram of effective intramolecular motion and ineffective intramolecular motion, the overlap of the optimized ground state (blue) and excited state (green) geometries of PyBT and PyBT-Pt-THD in the gas state, showing the changes in intramolecular vibration modes, RMSD values ​​and dihedral angles; c is the theoretical estimate of the total reorganization energy; d is the change of reorganization energy and Huang Lisi factor with frequency; e is the energy level diagram of spin-orbit coupling (SOC) matrix elements; f is a mechanism explanation; g is the distribution of natural transition orbits of T1 and T2 states;

[0086] exist Figure 7 In the figure, a is an energy level diagram, b is the molecular structure of the energy transfer material, c, d, and e are EL spectrum, EQE-brightness curve, emitter current density-voltage-brightness curve, and summary of 500-590nm wavelength materials reported in the literature; f is the summary of the maximum EQE of this work and reported solution-processed phosphorescent OLEDs; g is the summary of the EQE of this work and reported vacuum vapor deposition OLEDs at 1000cdm-2; h is the working life of the PyBT-Pt-THD device doped with 2% in 26DCzPPy at an initial brightness (L0) of 1000 and 5000cdm-2 and a constant current density of 10mAcm-2.

[0087] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. AIE-HLCT ligands are used to construct highly efficient solution-processable platinum complex luminescent materials, characterized in that: include: Aggregation-induced hybrid localized charge transfer (AIE-HLCT) material N,N'-(pyrimidine-4,6-diylbis(4,1-phenylene))bis(N-([1,1'-biphenyl]-4-yl)-[1,1'-biphenyl]-4-amine) as C^N bidentate ligand; The auxiliary ligand is 2,2,6,6-tetramethyl-3,5-heptanedione which has a solubilizing function; The structural framework exhibits an asymmetric vibration mode; The chemical structure of the luminescent material is shown below:

2. The AIE-HLCT ligand for constructing an efficient solution-processable platinum complex luminescent material according to claim 1, characterized in that: The spatial stacking form of the luminescent material is a spiral configuration.

3. The use of the AIE-HLCT ligand according to claim 1 to construct an efficient solution-processable platinum complex luminescent material, characterized in that: It is used as a dopant for luminescent materials in preparing the luminescent layer of solution-processed luminescent devices.

4. The use of the AIE-HLCT ligand in constructing a highly efficient solution-processable platinum complex luminescent material according to claim 3, characterized in that: The solution-processed light-emitting device has a light-emitting wavelength of 562 nm in a 2 wt % doped 26DCzPPy film, a maximum external quantum efficiency of 35.3%, and a maximum external quantum efficiency of 29.1% at a brightness of 5000.